Value-adding activities of venture capital companies: a content analysis of investor's original documents in Germany. Issue 3 (3rd July 2017) - Proksch, Dorian; Stranz, Wiebke; Röhr, Nino; Ernst, Cornelia; Pinkwart, Andreas; Schefczyk, Michael
Abstract: As many studies have shown, venture capital companies pursue value-adding activities for their portfolio firms to achieve abnormal returns compared to the market. Value-adding activities are complex and highly diverse, but also are very relevant to practice. Hence, the topic has been considerably analyzed in academic literature. However, there continues to be a lack of in-depth knowledge because of the sensitivity and scarcity of publicly available data from venture capital companies. We provide in-depth insights into the practices of venture capital companies. Using a longitudinal data-set obtained from nine venture capital companies in Germany, we qualitatively analyzed their value-adding activities. Drawing on investors' original documents, including business plans, investment committee papers, reports and annual statements of the investments, we created a typology of which value-adding services were performed. Results suggest that, consistent with prior studies, venture capital companies are highly engaged in supporting ventures with respect to financial and human capital issues as well as in establishing strong governance mechanisms to reduce information asymmetries between founders and investors. Venture capital companies also make moderate use of their network of relevant contacts. Support for operational issues is low.